AI-deation: When the Teacher is a Transformer in Role-Playing to create Privacy Decision Serious Games - Patrick Jost (Serious Games Society, 2024)
Understanding the synergistic potential of human collaboration with artificial intelligence (AI) in creative endeavours, such as ideating Serious Game (SG) concepts, is of vital interest in our era of digital transformation. This study probes two pivotal questions: First, how does the incorporation of a GPT-4 transformer AI, assuming the role of a teacher, influence support for student teams during the ideation and balancing of SG concepts? Second, what are the students' perceptions of AI integration when co-designing these concepts with an AI in the educator role? In a between-group research design, two distinct groups engaged in a collaborative role-playing activity with digital role-specific cards and a visualised board to ideate and balance Serious Games addressing privacy decision-making. The first group, engaging in a local setting, collaborated with an AI that played the teacher role. In contrast, the second group played the co-ideation activity in a remote setting, with a human playing the role of the teacher. The findings indicate that generative AI can successfully be sourced to play the teacher role in a collaborative role-playing activity. Crucially, the timing of AI intervention thereby emerged as an essential factor that can impair creative support. Scheduled AI interventions can offer fresh insights but may not align with immediate team needs. The insights underscore the requirement to determine the most effective timing for AI intervention in human-AI co-playing ideation sessions to foster the full potential of an AI filling a role in a collaborative design process. Implications synthesised from the analytical findings and practical insights on AI-suggested design propositions/conflicts are discussed conclusively.